2003
DOI: 10.1021/ma030021o
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Sphere-Type Monodispersed Oligosaccharide−Polypeptide Dendrimers

Abstract: A sphere-type fully substituted oligosaccharide-β-alanine-poly(lysine) dendrimer having a sharp molecular weight distribution was synthesized. Sphere-type poly(lysine) dendrimers were prepared using 1,4-diaminobutane as an initiator core and N,N′-bis(tert-butyloxycarbonyl)-L-lysine as a branching unit. β-Alanine was bound to the poly(lysine) dendrimer generation 3 to form β-alanine-poly(lysine) dendrimer generation 3, which has 16 terminal amino groups on its surface. A series of sphere-type oligosaccharide-β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 31 publications
1
40
0
Order By: Relevance
“…Scheme 1 indicates the synthesis route of the cellobiose-C6 spacer-polylysine dendrimer third generation ( ). According to our previous papers [8,18], 1, 4-diaminobutane was condensed with di-boc-lysine by BOP and DIEA reagents to give a first generation lysine dendrimer ( ) in 75% yield. After removal of the boc groups, di-boc-lysine was repeatedly condensed and the boc-protected groups deprotected with 2N TFA to give second and third generation polylysine dendrimers ( ) and ( ) in 82% and 83% yields from ( ) and ( ), respectively.…”
Section: Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scheme 1 indicates the synthesis route of the cellobiose-C6 spacer-polylysine dendrimer third generation ( ). According to our previous papers [8,18], 1, 4-diaminobutane was condensed with di-boc-lysine by BOP and DIEA reagents to give a first generation lysine dendrimer ( ) in 75% yield. After removal of the boc groups, di-boc-lysine was repeatedly condensed and the boc-protected groups deprotected with 2N TFA to give second and third generation polylysine dendrimers ( ) and ( ) in 82% and 83% yields from ( ) and ( ), respectively.…”
Section: Measurementsmentioning
confidence: 99%
“…Previously, we reported the synthesis of a spheretype polylysine dendrimer with a maltose unit by reductive amination between the maltose reducing end and the terminal amino group of the dendrimer [8]. It was revealed that all amino groups in the polylysine dendrimer having 16 amino groups were completely replaced by maltose to give a polylysine dendrimer having 32 maltose units.…”
Section: Scheme 1 Synthesis Of Third Generation Cellobiose-c6-spacer-mentioning
confidence: 99%
See 1 more Smart Citation
“…We synthesized sugar-containing poly(lysine) dendrimers for an HIV vaccine by directly introducing lactose, maltose, cellobiose or maltotriose to poly(lysine) dendrimer through a simple reductive amination. [36][37][38] Fully substituted, sugar-containing poly(lysine) dendrimers were obtained when activation of terminal amino group was performed. [37] In this kind of sugar-containing dendrimers, the nonreducing sugar residue is directed outwards.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38] Fully substituted, sugar-containing poly(lysine) dendrimers were obtained when activation of terminal amino group was performed. [37] In this kind of sugar-containing dendrimers, the nonreducing sugar residue is directed outwards.…”
Section: Introductionmentioning
confidence: 99%